Rectal bleeding. Issue 11 (November 2022) - Bonner, Clare; Pickering, George A E
This article aims to cover the presentation and management of rectal bleeding in adults, in sufficient breadth and depth for the GP trainee, recently qualified GPs, GP trainers and other allied health professionals consulting with patients in primary care. Rectal bleeding is a common reason for patients to consult their GP, urgent care centre or emergency department. The aetiology and variable presentations can pose a significant challenge to the primary care clinician. We hope this article will refresh background understanding and guide the assessment and management of these patients.